2003
DOI: 10.1037/0002-9432.73.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Structured group therapy for posttraumatic stress disorder in incarcerated male juveniles.

Abstract: This is the first study to evaluate the efficacy of a structured group therapy for posttraumatic stress disorder (PTSD) in incarcerated male juveniles. Ten groups of juveniles (n = 45) completed a 12-session intervention with pre- and postassessments composed of the Post Traumatic Stress Disorder Reaction Index (C. Frederick, 1985) and supplementary measures of anxiety, anger, and depression. Overall, group participants experienced significant reductions in self-reported PTSD symptoms. Supplemental analyses su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 35 publications
1
57
0
Order By: Relevance
“…These results are consistent with the findings of Ovaert et al (2003) who assert was the first controlled study to evaluate the efficacy of a structured cognitive behavioral therapy program for traumatized incarcerated youth. The researchers used a measure of post-traumatic stress PTSD-RI (Frederick, 1982) that is somewhat similar to the CAQ.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are consistent with the findings of Ovaert et al (2003) who assert was the first controlled study to evaluate the efficacy of a structured cognitive behavioral therapy program for traumatized incarcerated youth. The researchers used a measure of post-traumatic stress PTSD-RI (Frederick, 1982) that is somewhat similar to the CAQ.…”
Section: Discussionsupporting
confidence: 82%
“…The study discussed earlier (Ovaert et al, 2003) did not demonstrate reductions in symptoms of anxiety, anger and depression. Goenjian (1997), in a study of the outcome of psychotherapy among early adolescents after trauma, similarly did not report reductions in depression after trauma treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Office for National Statistics Health Survey (2001) found that the spectrum of behaviour problems (from disruptive behaviour to autistic spectrum disorder) to be present in 7.4% boys and 3.2% girls in the U.K. Ovaert et al (2003) suggests links between behaviour problems and mental health issues associated with post traumatic stress. They assert that causative trauma may be overlooked or neglected in the face of problems in school caused by the behaviour.…”
Section: Figure 3: Summary Of Findings Research Studies Reviewedmentioning
confidence: 99%
“…Anxiety can have far reaching effects on school attendance, learning, achievement and peer relationships. One systematic review (Compton et al 2002); two experimental studies (Mendlowitz et al 1999, Pfeffer et al 2002 and five simple before and after studies (Benazon et al 2002, March et al 1998, Kaplan et al1995, Ovaert et al 2003, Thieneman et al 2001) provided evidence of effectiveness of CBT counselling for emotional problems related to anxiety. Compton et al (2002) provided evidence of effectiveness of CBT in the 6-13 years age group with generalized anxiety, separation anxiety, social anxiety and avoidant disorder and showed effectiveness in reducing 08 108 •…”
Section: Figure 3: Summary Of Findings Research Studies Reviewedmentioning
confidence: 99%